BECOMING CHARRÚA EN EL URUGUAY: challenges of collaborative ethnography in contexts of indigenous re-emergence - Rodríguez, Mariela Eva (Universidade de Brasília, 2018)
Book review: Olivera, A. Devenir charrúa en el Uruguay: una etnografía junto con colectivos urbanos. Montevideo: Lucida editores y Fondation pour l’Université de Laussane, 2016,